Unges selvskadende adfærd - 2000-2015 og muligheder for forebyggelse - Zølner, Lilian (Psyke & Logos, 2016)
Suicide, attempted suicide and self-harming behaviour among adolescents has been debated since 2000. Unfortunately, no significant decline in suicide rates has been documented since 2007; neither has there been a notable fall in the attempted suicide rates among adolescents aged 10-19. The number of adolescents who commit self-harm has risen since 2001. This development challenges research to shift focus from risk factors in order to gain knowledge on circumstances that prevent and protect adolescents against serious suicide ideation and suicide attempts. All adults may contribute to inspire hope and spirit among adolescents. This does not mean that adults must cater to the adolescent’s every wish and expectations. It means that adults must encourage the adolescent to endure those sorrows, losses, defeats and injustices that life dishes out when we least expect it.